Pengaruh Kepemimpinan Demokratis, Lingkungan Kerja Non Fisik, dan Kompensasi Finansial terhadap KepuasanKerja Karyawan PT. PLN UP3 Surabaya Selatan - Hanif Ardhi Pranata; Bowo Santoso (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the influence of democratic leadership, the non-physical work environment, and financial compensation on employee job satisfaction at PT PLN UP3 South Surabaya. The research method used a quantitative approach, with data collected through questionnaires distributed to 60 respondents, representing all employees. Data were analyzed using the Partial Least Squares (PLS) method with the assistance of SmartPLS. The results indicate that democratic leadership, the non-physical work environment, and financial compensation have a positive and significant effect on employee job satisfaction, with financial compensation being the most dominant variable. The conclusion of this study is that the better the implementation of democratic leadership, the more conducive the non-physical work environment, and the fairer and more timely the financial compensation provided, the higher the level of employee job satisfaction at PT PLN UP3 South Surabaya.   Keywords: Democratic Leadership, Job Satisfaction, Financial Compensation, Non-Physical Work Environment